2022
DOI: 10.3390/scipharm90030041
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Approach for the Application of Hibiscus sabdariffa Extract Ointment in the Superficial Burn Care

Abstract: Wound healing comprises organized events involving tissue repair and regeneration. The discovery of toll-like receptors (TLRs) sheds recent light on the mechanisms involved in initiating inflammatory responses throughout the healing cascades. Hibiscus sabdariffa (HS) components may exhibit a wound healing action, owing to their antioxidant and anti-inflammatory activities. This study was designed to investigate the early effects of HS loaded in an ointment base on wound healing, antioxidant, antimicrobial effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Recently, some antioxidant-rich natural products were examined for their impact on wound healing. It has been shown that some of them induce an increase in tissue repair, which is accompanied by increased levels of wound contracture, hydroxyproline, hexosamine, fibrocytes, fibroblasts, as well as better re-epithelialization, higher collagen deposition, enhanced fibronectin content, and enhanced fibroblast cells [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some antioxidant-rich natural products were examined for their impact on wound healing. It has been shown that some of them induce an increase in tissue repair, which is accompanied by increased levels of wound contracture, hydroxyproline, hexosamine, fibrocytes, fibroblasts, as well as better re-epithelialization, higher collagen deposition, enhanced fibronectin content, and enhanced fibroblast cells [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stocks were maintained in 20% ( v / v ) glycerol at −80 °C until needed. Bacterial strains were grown on Cetrimide agar (Sigma-Aldrich, St. Louis, MO, USA) overnight at 37 °C [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a polysaccharide-enriched crude extract from H. sabdariffa flower potently stimulated the proliferation of cultured keratinocytes [153], which may explain the addition of these preparations to H. sabdariffa skin care products. As well, a water in oil cream of the methanol extract of the calyces has been prepared as a potential commercial wound healing substance [154,155]. Preparations from H. sabdariffa calyx are also traditionally used in various countries including Suriname, for treating a broad range of conditions such as microbial infections, cough and bronchitis, kidney problems, various gastrointestinal conditions, and hypertension [49,151,156,157].…”
Section: Antioxidant Vitamins: Vitamin E: Hibiscus Sabdariffa L (Malv...mentioning
confidence: 99%